SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN “BEST AGENT” DENGAN METODE PROFILE MATCHING (GAP) - Maulana, Brian Arif; Budiyantara, Agus (Infotech: Journal of Technology Information, 2019)
The problem of selecting the "Best Agent" is still done manually, by giving a value to the form that contains the assessment criteria and the sum of the values of each criterion that is averaged so that the final result is obtained. The purpose of this study is to discuss and build systems and models for making decisions to determine the "Best Agent" using the Profile Matching method. Application Decision Support System Selection "Best Agent" Profile Matching method an application designed to provide accurate decisions based on current data and can be accounted for, this is expected to improve the quality of staff and the expectations it builds to improve the quality of Human Resources.